(untitled) (Medico Legal Update, 2020)
Introduction: Leprosy is an infectious disease that causes various problems, not only in medical terms but also extends to social, economic, cultural, security and social security issues. Efforts made to break the chain of transmission of leprosy cases focus more on individuals who have not focused on families that have a high transmission chain. Purpose: The research aims to explore the social factors of social and cultural factors in influencing family independence in preventing transmission of leprosy, describing the independence of the family in preventing transmission of leprosy, then compiled an example of a culture-based family independence program model for the prevention of leprosy transmission in Sampang with a theoretical approach used namely Family Centered Nursing and the theory of Transcultural Nursing in the form of modules. Method: This study uses a qualitative research approach. Data saturation until five participants were obtained who carried out data retrieval in an in-depth interview. Data analysis using the Collaizi analysis method. Results: Identification found four main themes: ((1) Religious; (2) Social Factors; (3) Economic Factors; and (4) Cultural Value. Conclusions: The description of the independence of families who care for lepers is still influenced by many factors, especially tradition and culture, efforts to break the chain of transmission are also closely related to care efforts that still do not reflect preventive values.